2023
DOI: 10.1021/acsmacrolett.3c00139
|View full text |Cite
|
Sign up to set email alerts
|

A Directional Chitosan Sound Sensor Based on Piezoelectric–Triboelectric Sensing

Abstract: Herein, we have constructed a directional sound sensor based on an anisotropic chitosan aerogel. Because of the lamellar porous structure, this chitosan aerogel exhibits a distinct anisotropic behavior, featuring the compressive stress along the direction of the parallel laminate structure, being approximately 2.6 times that in the orthogonal direction. Simultaneously, the chitosan aerogel is used as a directional sound-sensing material, which exhibits excellent acoustic–electric conversion performance with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Moreover, the position and intensity of the voltage waveform precisely matched with the waveform of the sound source. This result indicates that the Gly-Alg-Glycerol piezoelectric film developed here has potential for application in artificial cochlea [ 48 ].…”
Section: Resultsmentioning
confidence: 89%
“…Moreover, the position and intensity of the voltage waveform precisely matched with the waveform of the sound source. This result indicates that the Gly-Alg-Glycerol piezoelectric film developed here has potential for application in artificial cochlea [ 48 ].…”
Section: Resultsmentioning
confidence: 89%
“…In this regard, the easy processability, flexibility, biocompatibility, and chemical robustness of piezoelectric polymers render them excellent candidates to be integrated into small and lightweight devices for energy harvesting applications. 10–14 Though polymers such as polyvinylidene fluoride (PVDF) and their copolymers such as polyvinylidene fluoride trifluoroethylene (PVDF-TrFE) and poly(vinylidene fluoride-co-hexafluoropropene) (PVDF-HFP), 15,16 odd nylons, 1,2,17–20 poly (lactic acid), 4 cellulose, 21,22 chitosan, 23 polyhydroxybutyrate, 24 etc. , are known to exhibit the piezoelectric effect, most of the earlier studies were focussed on PVDF and their copolymers, as they exhibit superior piezoelectric performance.…”
Section: Introductionmentioning
confidence: 99%
“…40 Recently, many groups have focussed on the design and fabrication of three-dimensional porous ceramics, polymers and composite-based piezoelectric devices. 12,23,41–46 Porous piezoelectric materials were reported to show high output sensitivity and a higher piezoelectric harvesting figure of merit over dense materials. 47 Previous studies demonstrated that porous materials featuring a lower modulus have improved compression deformation and also the emergence of local stress hot spots improved the output performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abundant evidence has shown that the number and size of pores are crucial for defining the behavior of materials. Additionally, the porous structure of PPMs not only creates a rough surface but also offers an immense internal surface area, which might be beneficial for generating additional charges [44,45].…”
Section: Introductionmentioning
confidence: 99%